Roles of Family Stress, Maltreatment, and Affect Regulation Difficulties on Adolescent Mental Health During COVID-19 - Craig, Stephanie G. (Journal of family violence, 2022)
This study examines the indirect effects of affect dysregulation and suppression on the associations between family stress from confinement, maltreatment, and adolescent mental health during COVID-19. We examined both adolescent and caregiver perspectives to yield a more well-rounded understanding of these associations than afforded in previous research. Using both adolescent (N = 809, Mage = 15.66) and caregiver (N = 578) samples, family stress from confinement, exposure to physical and psychological maltreatment, affect dysregulation and suppression, and youth internalizing and externalizing symptoms were measured in the summer of 2020, following three months of stay-at-home orders due to COVID-19. Affect dysregulation partially accounted for the associations between family stress from confinement and psychological maltreatment on both internalizing and externalizing symptoms for youth and caregiver report. Suppression partially accounted for the associations between family stress and maltreatment on internalizing and externalizing symptoms in the youth sample, but only for internalizing symptoms in the caregiver sample. Understanding family predictors of adolescents’ mental health concerns and their underlying mechanisms, affect dysregulation and suppression, can inform mental health interventions during and following the COVID-19 pandemic.